PEMANFAATAN E-LEARNING SEBAGAI MEDIA PEMBELAJARAN - Ranius, Ahmad Yani (Universitas Bina Darma, 2013)
IT-based learning called e-learning is the process of transforming conventional education into digital form. Use of e-learning as a medium of learning is based on the characteristics of e-learning consists of non-linearity, self-managing, Feedback, interactivity, multimedia-style Leaners, Just in Time, Dynamic Updating, Accesibility and Colaborative Learning Easy. Using a descriptive design with questionnaires as research instruments. The number of sample of 100 respondents with a student population of the semester study program Information Systems 5 (five). It was concluded that the use of e-learning as a medium of learning at the University of Bina Darma in condition Quite Satisfied with the percentage of 60%. Eight characteristics: Non-linearity, self-managing, Just in Time, and Easy Self Accesibility already satisfied the conditions. While the characteristics of the feedback, interactivity, multimedia-style Leaners, Dynamic Updating, and Colaborative Learning has not satisfied the conditions. Keywords: Information Technology, E-Learning